Nursing Care for Postoperative Transsphenoidal Pituitary Tumor Resection Patients - Nuangkanya, Montira; Butsing, Nipaporn (NU Journal of Nursing and Health Sciences, 2020)
Transsphenoidal surgery is the most common approach to remove pituitary tumors. Management of patients following transsphenoidal pituitary tumor resection can be challenging for nurses. Transsphenoidal surgery for pituitary tumor resection is complicated and linked with several body systems. Successful postoperative transsphenoidal surgery management needs expert nursing care for early identification and prompt management of complications. Appropriate and timely management can save patient's lives and get the best recovery from pituitary tumor surgery. This article reviewed knowledge on pituitary adenomas, postoperative complications, and guidelines for nurses caring for patients postoperative transsphenoidal pituitary tumor surgery. The materials included assessment and nursing management of rebleeding and increased intracranial pressure, visual disturbances, pituitary apoplexy, cerebrospinal fluid leak, meningitis, epistaxis, diabetes insipidus, hyponatremia, syndrome of inappropriate antidiuretic hormone, cerebral salt wasting syndrome, adrenal insufficiency, and discharge instructions for patients with transsphenoidal pituitary tumor resection.